2015
DOI: 10.1007/s40263-015-0272-9
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl Cysteine (NAC) in the Treatment of Obsessive-Compulsive Disorder: A 16-Week, Double-Blind, Randomised, Placebo-Controlled Study

Abstract: ACTRN12613000310763.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 36 publications
1
53
0
1
Order By: Relevance
“…N‐acetylcysteine was effective in therapy of OCD, further implicating the glutamate pathway (Lafleur, Pittenger, Kelmendi, et al, ; Oliver et al, ; Paydary, Kamaloo, Ahmadipour, et al, ). Sarris et al showed that N‐acetylcysteine reduced the compulsive subscale of YBOCS significantly, although it was not as effective in reducing the obsessive subscale (Sarris, Oliver, Camfield, et al, ). This effect further supports the role of glutamate modulation on compulsive behavior (Ghanizadeh, Derakhshan, & Berk, ; Grant, Kim, & Odlaug, ).…”
Section: Discussionmentioning
confidence: 99%
“…N‐acetylcysteine was effective in therapy of OCD, further implicating the glutamate pathway (Lafleur, Pittenger, Kelmendi, et al, ; Oliver et al, ; Paydary, Kamaloo, Ahmadipour, et al, ). Sarris et al showed that N‐acetylcysteine reduced the compulsive subscale of YBOCS significantly, although it was not as effective in reducing the obsessive subscale (Sarris, Oliver, Camfield, et al, ). This effect further supports the role of glutamate modulation on compulsive behavior (Ghanizadeh, Derakhshan, & Berk, ; Grant, Kim, & Odlaug, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another antibiotic, cefdinir, was studied, but it showed no effectiveness on the CY-BOCS scores when compared to a placebo [171]. Finally, N-acetylcysteine (NAC), an antioxidant which has a neuroprotective role against oxidative stress, produced divergent results [139,140,141,142,143] (Table 5). …”
Section: Alternative Treatments For Ocdmentioning
confidence: 99%
“…Asimismo, una revisión sistemática sostiene que la NAC reduce la severidad de los síntomas del TOC y trastornos relacionados con un buen perfil de tolerabilidad y mínimos efectos adversos (54). Sin embargo, otro EADCCP no indica resultados concluyentes (55).…”
Section: Fármacos Relacionados a La Función Glutamatérgicaunclassified